(untitled) (Dhaka University Journal of Biological Sciences, 2019)
Bagarius bagarius (Hamilton, 1822), a freshwater catfish species, is important as food and game fish in Bangladesh, Bhutan, India and Nepal. In Bangladesh, it is known as Baghair and has been enlisted as critically endangered (CR) species in the IUCN Red List of Bangladesh 2000 and 2015, under the criteria A2cd version 3.1 mentioning declining trend in its population around 80% during the last 25 years (3 generation time). We studied the abundance of B. bagarius at 8 sites in three riverine habitats. We identified 8 individuals of B. bagarius from the Meghna river only (Shibpur site, Bhola Sadar). However, focus group discussion with fishers revealed that the species was frequently present in the catch from the river, although the abundance reduced considerably over the decade. We also found several other studies which reported the abundance of B. bagarius in different natural habitats. The findings from this study in combination with other published literature in the last 5 years indicated that the current status of B. bagarius in natural waters in Bangladesh do not fall below the threshold limits of CR species. Therefore, B. bagarius should be reclassified into a lower threatened status (but not Least Concern) than the current CR. Dhaka Univ. J. Biol. Sci. 28(1): 111-119, 2019 (January)